Regularity of the 3D Navier–Stokes equations with viewpoint of 2D flow - Bae, Hyeong Ohk (Journal of Differential Equations, 2018)
The regularity of 2D Navier–Stokes flow is well known. In this article we study the relationship of 3D and 2D flow, and the regularity of the 3D Naiver–Stokes equations with viewpoint of 2D equations. We consider the problem in the Cartesian and in the cylindrical coordinates.
Keywords: 2D flow; 3D flow; Axisymmetric flow; Regularity; Swirl